Impact of the method and success of pharyngeal reconstruction on the outcome of treating laryngeal and hypopharyngeal cancers with pharyngolaryngectomy: A national analysis. Issue 5 (May 2017) - Nouraei, S.A.R.; Dias, A.; Kanona, H.; Vokes, D.; O'Flynn, P.; Clarke, P.M.; Middleton, S.E.; Darzi, A.; Aylin, P.; Jallali, N.
Summary: Background: Surgical treatment of cancers that arise from or invade the hypopharynx presents major reconstructive challenges. Reconstructive failure exposes the airway and neck vessels to digestive contents. Methods: We performed a national N = near-all analysis of the administrative dataset to identify pharyngolaryngectomies in England between 2002 and 2012. Information about morbidity, pharyngeal closure method and post-operative complications was derived. Results: There were 1589 predominantly male (78%) patients whose mean age at surgery was 62 years. The commonest morbidities were hypertension (24%) and ischemic heart disease (11%). For 232 (15%) patients, pharyngolaryngectomy was performed during an emergency admission. The pharynx was closed primarily in 551 patients, with skin or muscle free or pedicled flaps in 755 patients and with jejunum and gastric pull-up in 123 and 160 patients, respectively. In-hospital mortality rate was 6% and was significantly higher in the gastric pull-up group (11%). Reconstructive failure had an odds ratio of 6.2 [95% confidence interval (CI) 2.4–16.1] for in-hospital death. The five-year survival was 57% and age, morbidities, emergency surgery, gastric pull-up, major acute cardiovascular events, renal failure and reconstructive failure independently worsened prognosis. Patients who underwent pharyngeal reconstruction with radial forearm or anterolateral thigh flaps had lower mortality rates than patients who had jejunum flap reconstruction (hazard ratio = 1.50 [95% CI 1.03–2.19]) or gastric pull-up (hazard ratio = 1.92 [95% CI 1.32–2.80]). Conclusions: Pharyngolaryngectomy carries a high degree of risk of morbidity and mortality. Reconstructive failure worsens short- and long-term prognosis, and the use of cutaneous free flaps appears to improve survival.